Iridium-Catalyzed Synthesis of ω-Hydroxy Homoallylic Alcohols - Obora, Yasushi; Sawaguchi, Takuya; Tsubakimoto, Keiko; Yoshida, Hiroshi; Ogawa, Shinji; Hatanaka, Shintaro (Synthesis, 2013)
A novel process has been developed for the construction ω-hydroxy homoallylic alcohols via the iridium-catalyzed reaction of α,ω-diols with 2-alkynes such as 1-arylprop-1-ynes.
Keywords: iridium catalyst; ω-hydroxy homoallylic alcohol; diol; transfer hydrogenation; 1-arylprop-1-yne